Application of Constructivism Method in Islamic Religious Education for Development Skills Think Critical and Religious Student - Afi Parnawi; Tri Gunawan; Farid Naya; Alwiyah, Alwiyah (International Journal of Education, Vocational and Social Science, 2025)
Study This aiming For explore implementation theory Study constructivist in Islamic Religious Education (PAI) as well analyze How approach This push active and reflective learning . Learning theory constructivist focuses on learning based on experience , interaction social , and reflection , allowing student For build knowledge they in a way independent . The research method used is approach qualitative with design studies case . Data collected through interview deep with PAI teachers, students , and principals school , observation class , and analysis document learning like Plan Learning Implementation (RPP) and teaching modules . Research results show that PAI teachers implement various learning strategies constructivist , including learning based on problem -based learning, discussion group , learning based on projects , and usage technology interactive . Implementation of this strategy proven increase involvement active students , develop skills think critical , and facilitate deep reflection related implementation Islamic teachings in life daily .